Sistem Informasi Logbook Berbasis Web Pada Stasiun Geofisika Kelas I Deli Serdang - Al Fasih, Faisal; Nisa, Khairrun (CV. Hawari, 2023)
In today's digital era, the use of information technology is very important to increase efficiency and convenience in various fields, including logbooks. The purpose of this article is to design a web-based logbook information system at the Class I Geophysical Station Deli Serdang which will facilitate employees in filling in the Synop logbook and Absolute Observation. The method used in this study is the waterfall development method which consists of five stages, namely need identification, system design, preparation of program code, program testing, and program implementation. Further during the creation of the program using Visual Studio Code, Laravel Framework 10, PHP and using XAMPP as a database. From these checks, it is known that the website is functioning as it should. The web-based Logbook Information System at the Class I Geophysical Station Deli Serdang provides convenience and efficiency for employees who carry out services.